The hELENa project: I. stellar populations of early-type galaxies linked with local environment and galaxy mass - Sybilska, Agnieszka; Lisker, Thorsten (Monthly notices of the Royal Astronomical Society, 2017)
We present the first in a series of papers in The role of Environment in shaping Low-mass Early-type Nearby galaxies (hELENa) project. In this paper, we combine our sample of 20 low-mass early types (dEs) with 258 massive early types (ETGs) from the ATLAS3D survey - all observed with the SAURON integral field unit - to investigate early-type galaxies' stellar population scaling relations and the dependence of the population properties on local environment, extended to the low-σ regime of dEs. The ages in our sample show more scatter at lower σ values, indicative of less massive galaxies being affected by the environment to a higher degree. The shape of the age-σ relations for cluster versus non-cluster galaxies suggests that cluster environment speeds up the placing of galaxies on the red sequence. While the scaling relations are tighter for cluster than for the field/group objects, we find no evidence for a difference in average population characteristics of the two samples. We investigate the properties of our sample in the Virgo cluster as a function of number density (rather than simple clustrocentric distance) and find that dE ages correlate with the local density such that galaxies in regions of lower density are younger, likely because they are later arrivals to the cluster or have experienced less pre-processing in groups, and consequently used up their gas reservoir more recently. Overall, dE properties correlate more strongly with density than those of massive ETGs, which was expected as less massive galaxies are more susceptible to external influences.
Gesehen am 18.10.2017